UJI LINEARITAS MENGGUNAKAN STATISTICAL PRODUCT AND SERVICE SOLUTIONS (SPSS) UNTUK MAHASISWA SEMESTER VII (TUJUH) FAKULTAS ILMU BUDAYA UNIVERSITAS LANCANG KUNING - Yuhelmi, Yuhelmi (Aksara Public, 2018)
Based on our findings in the field there are still many students who have not understood yet and can not use SPSS (Statistical Product And Service Solution) especially in doing Linearity Test where in their mind better make qualitative research than quantitative research because in their mind using SPSS is difficult, because processed resulting from the SPSS output they do not understand, nor do they know the steps to test the Linearity with the SPSS, and few students end up using the SPSS application program to process their research data. So our team of devotion felt called to be able to carry out this community service because they feel responsible for the success of our students in education with utilization of computer technology, besides that I as a lecturer course Research Methods of the last few years should be able to transfer the knowledge that I have so they can complete the final task on time without the help of others services and will be brought later in the world of work. Before the training is done the team first gives a questionnaire to the participants to know their knowledge early about Linearity Test. The design of Ibm to be implemented is 1. Introduction and provision of training materials. 2. Submission of training materials, 3. Provision of Practice with computer, After completion of training the team again distributed the same questionnaire thus can be seen how much improvement their knowledge after the training is given by comparing the questionnaire before and the questionnaire after the training is given. So based on both pre test table and post test we can see the increasing ability of the participants after the training is given that is from correct 15 (14%) to 79(75%) correct answer, significant increase in ability.